Active Video Games and Low-Cost Virtual Reality: An Ideal Therapeutic Modality for Children With Physical Disabilities During a Global Pandemic - Demers, Marika; Martinie, Ophélie; Winstein, Carolee; Robert, Maxime T. (Frontiers in Neurology, 2020)
Current guidelines against spread of coronavirus (COVID-19) interrupt nonessential rehabilitation services. Thus, individuals with physical disabilities such as children with cerebral palsy can no longer benefit from physical rehabilitation during this undetermined period. Using either a synchronous or asynchronous format, in collaboration with a therapist via telerehabilitation, we suggest that active video games and low-cost virtual reality are a promising delivery mode for at-home rehabilitation in the context of a global pandemic. This therapeutic modality, incorporated into an at-home individualized treatment plan provides a means to lessen the impact of an interruption in rehabilitation services while not loosing the pre-pandemic, in-person physical activity gains. Growing evidence supports active video games and low-cost virtual reality as viable therapeutic interventions for children with physical disabilities. These technologies are especially well-accepted by pediatric populations for the ludic and motivating features that lend themselves to nearly seamless incorporation into telerehabilitation. Advantages for rehabilitation of active video games and low-cost virtual reality include a rich, challenging, multi-modal training environment in which high numbers of movement repetitions can be accomplished, and a unique opportunity to foster engaged practice actions that go beyond household activities. We offer suggestions for the clinician about how to adopt active video games and low-cost virtual reality into your practice during a global pandemic.